2019
DOI: 10.3390/nano9070924
|View full text |Cite
|
Sign up to set email alerts
|

Effective Modulation of Optical and Photoelectrical Properties of SnS2 Hexagonal Nanoflakes via Zn Incorporation

Abstract: Tin sulfides are promising materials in the fields of photoelectronics and photovoltaics because of their appropriate energy bands. However, doping in SnS2 can improve the stability and robustness of this material in potential applications. Herein, we report the synthesis of SnS2 nanoflakes with Zn doping via simple hydrothermal route. The effect of doping Zn was found to display a huge influence in the structural and crystalline order of as synthesized SnS2. Their optical properties attest Zn doping of SnS2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The 10% Mn doping leads to saturation of the magnetization with moderate applied fields in restacked exfoliated samples. The doping content of the materials reported here is much higher than the reported intralayer V-, Ti-, Zn-, Cu-, Sb-, and Fe-doped SnS 2 variants. , We not only successfully realize magnetic doping of SnS 2 , but also provide a promising methodology to harvest air stable magnetic nanosheets.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The 10% Mn doping leads to saturation of the magnetization with moderate applied fields in restacked exfoliated samples. The doping content of the materials reported here is much higher than the reported intralayer V-, Ti-, Zn-, Cu-, Sb-, and Fe-doped SnS 2 variants. , We not only successfully realize magnetic doping of SnS 2 , but also provide a promising methodology to harvest air stable magnetic nanosheets.…”
Section: Introductionmentioning
confidence: 70%
“…To expand SnS 2 -related applications, various SnS 2 derivatives were prepared using intercalation and dopant chemistry, which is a strategy for tuning the band gap and photoelectrical properties. Previous publications reported that the nonmagnetic elements V, Ti, Zn, Cu, and Sb can substitute for Sn, which lead to a wider solar absorption due to the decrease of band gap and enhanced photoelectronic performance. Compared to doping with nonmagnetic elements, magnetic doping mainly occurs in the vdW gap, while intralayer doping is much less investigated. The few existing reports in the literature are very intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…photoelectronic properties of SnS 2 -based heterostructures have been examined in the literature and have been proven to have an excellent performance [15][16][17]. The photoelectronic properties of SnS 2 have also received research attention [3,[19][20][21][22][23][24][25][26] due to the abundance, environmentally friendly qualities and energy gap of this material (∼2.28 eV for bulk, 2.6 eV for thin film <6 nm) [29], which falls within the range of visible light. However, these studies report either a large photoelectronic current (of the order of µA) with a long response time (seconds) or a small photoelectronic current (nA range) with a short response time (milliseconds).…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the Special Issue “Functional Nanostructures for Sensors, Optoelectronic Devices, and Drug Delivery” was to provide an overview of the current research activities in the field of nanostructured materials, with a particular emphasis on their potential applications for sensors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ], optoelectronic devices [ 10 , 11 , 12 , 13 , 14 , 15 ], and biomedical systems [ 16 , 17 , 18 ]. The Special Issue welcomed the submission of original research articles [ 1 , 2 , 3 , 4 , 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and comprehensive reviews that demonstrated or summarized significant advances in the above-mentioned research fields. Next, the Special Issue collected fifteen selected original research papers and three comprehensive reviews [ 7 , 8 , 18 ] on various topics of nanostructured materials and relative characterization spanning from fundamental research to technological applications.…”
mentioning
confidence: 99%
“…They demonstrated that these nanostructured materials show higher visible-light absorption and significant improvement in conductivity and sensitivity to illuminations, compared to pristine SnS 2. Such an excellent performance of Sn 0.97 Zn 0.03 S 2 nanoflakes was reported for potential application in optoelectronic devices [ 12 ].…”
mentioning
confidence: 99%